Development and validation of the ethical challenges in clinical situations-questionnaire (ECCS-Q) by involving health-care providers from a tertiary care health setting. (June 2022) - Gupta, Snehil; Singh, Swarndeep; Sarkar, Siddharth; Batra, Atul
Background and rationale: Clinicians often encounter a variety of ethical challenges in their routine clinical practice, and it varies across healthcare and cultural settings of their practice. Despite of this, there are no clear-cut available guidelines concerning the right course of action in a given ethically challenging situation. A validated instrument that could capture the health care providers' (HCP's) viewpoints in this regard is lacking from Indian settings. Thus, the current study aimed at developing an instrument to assess the HCP's perspective regarding different ethically challenging situations encountered in the Indian settings. Methods: The questionnaire was developed by involving 15 medical experts. A mixed-method approach, Delphi-technique, and online survey were used for item generation and validation. Results: The questionnaire comprised of 11 items (accounts 57% variance; having an α = 0.68) representing four factors: health-resource constraints, medical responsibility of the HCP, obtaining patients/family members' consent for the treatment, and treatment beyond the standard protocol. The gender and clinical disciplines of the participants were related to their level of endorsement for various domains of the ECCS-Q. Conclusions: Ethical challenges in the clinical practice fall in different clusters. The clinicians' course of action in such situations have many socio-demographic and professional determinants. Future studies are warranted to investigate these phenomena.